Analytical models for channel potential and drain current in AlGaN/GaN HEMT devices - Qian, Haisheng (2020)
Analytical models for channel potential and drain current in AlGaN/GaN HEMT devices are obtained. The analytical model results are verified against simulations, good agreements are observed. The explicit expression for drain current make the model suitable to be embedded in circuit simulation and design tools.